Facebook use and sleep quality: Light interacts with socially induced alertness. (5th October 2018) - Bowler, Jenny; Bourke, Patrick
Abstract : It has been demonstrated that the use of social networking sites late at night can lead to sleep‐related problems that extend into the next day. A common explanation is that the light emitted from screens is disrupting the users' circadian rhythms. An alternative explanation is that the social cognition inherent in the use of social networking sites is responsible. Here, the two factors were looked at together. Participants used Facebook on iPad tablets before sleep. This was done on different nights with two lighting conditions and with two levels of content. In the 'light' condition, blue wavelength light was manipulated so that it was either full wavelength or blue light filtered. In the 'alertness' condition, the personal significance of the content was changed from personally relevant to irrelevant. A modified version of the Pittsburgh Sleep Quality Index was used to measure sleep‐related problems. No evidence was found that simply filtering blue light or simply removing relevant content improved sleep quality. However, the two factors interacted. The results suggest that the light emitted from screens can affect sleep quality under some conditions but this is behaviourally irrelevant in the context of normal Facebook usage.